EVALUATION OF IgG ANTIBODIES AGAINST RESPIRATORY SYNCYTIAL VIRUS (RSV), AND ASSOCIATED RISK FACTORS FOR SEVERE RESPIRATORY TRACT INFECTIONS IN PRE- SCHOOL CHILDREN IN NORTH-CENTRAL, NIGERIA. - Faneye, Adedayo; Motayo, Babatunde O; Adesanmi, Adeyinka; Onoja, Bernard (African Journal of Infectious Diseases (AJID), 2014)
Background: Childhood mortality and morbidity due to RSV is increasing. Our current study was aimed at determining the sero-prevalence rate of RSV IgG antibodies and investigates certain known risk factors for RSV disease severity in infants and pre-school children presenting with various forms of respiratory tract infections in Ilorin, Nigeria. Materials and Methods: About 280, children and 30, aged matched controls were enrolled into the study at the specialist hospital Ilorin. Blood testing for anti RSV IgG was done using a commercial ELISA kit by IVD Research Inc® Carlsbad. California U.S.A. Information regarding Nutritional status, socio-economic status and other demographic variables were collected. Results: A prevalence rate of 85.7% was recorded among tested children and 23.3%, in controls, across age groups and gender. A statistically significant difference in age groups were recorded among patients with LRTI, (p <0.05), age <1 41%, age 1 <5, 27.6%. This was also the case for children with SRTI (Pneumonia and Bronchiolitis), with age < 1yr, 9%, and 1 <5yr, 19.8%. Analysed risk factors for disease severity showed thatnutritional status of children were statistically significant for disease severity, p-value, 0.039 (Chi square test). Conclusions: We report a high level of exposure to RSV in infancy and early childhood among children from a representative population in a major central Nigerian City, further studies into neutralising antibody levels and subtype distribution of RSV are advocated.